Radical-scavenging activity and antibacterial activity of the crude ethanolic leaf extract of Pangyawan (Tinospora rumphii). - Quillotes, Balvin C.; Ricarte, Marjhun A. (Balvin C. Quillotes, 2018)
T. rumphii is known for its numerous traditional recipes in which according to traditional folklores are capable of curing several diseases and illnesses like diabetes, skin itches and gastrointestinal ailments. In this study, the radical scavenging-activity and antibacterial activity of the crude ethanolic leaf extract of T. rumphii were evaluated. Using the DPPH (2,2-diphenyl-l-picrylhydrazyl) radical scavenging assay with Quercetin and Gallic acid as reference standards, the in vitro radical scavenging capacity of the extract was assessed. Results showed that the radical scavenging activity of the extract was very low, with SC50 = 2058.00 +/- 32.66 ppm, relative to the standards used, Gallic acid SC50= 6.67 +/- 0.12 ppm and Quercetin SC50= 4.75 +/- 0.19 ppm. The antibacterial activity of the extract was also evaluated using the disk diffusion method. The results showed that the extract exhibited an antibacterial activity against Staphylococcus aureus and Eschirichia coli. However, larger zone of inhibitions was observed on the extracts assayed against S. aureus (gram negative). Thin layer chromatographic analyses were conducted to elucidate and partially identify the phytochemicals responsible for the observed scavenging activity and antibacterial activity. Results of the TLC suggested the presence of plant phenolics and flavonoids which could be accounted for the activities observed.
A research paper (B.S. Biology) -- University of the Philippines, Tacloban.